Empowering Patients in the Therapeutic Decision-Making Process: A Glance Into Behçet's Syndrome - Marinello, Diana; Di Cianni, Federica; Del Bianco, Alessandra; Mattioli, Irene; Sota, Jurgen; Cantarini, Luca; Emmi, Giacomo; Leccese, Pietro; Lopalco, Giuseppe; Mosca, Marta; Padula, Angela; Piga, Matteo; et al. (Frontiers in Medicine, 2021)
Behçet’s syndrome (BS) represents a challenging condition, characterized by a variable spectrum of disease profile and associated with a significant limitation of the daily activities as well as a potential negative impact on relationships and psychological status. Considering also the complexity of the therapeutic management of BS, that often includes biological off-label treatments, the participation in the therapeutic decision-making process of the BS patients is essential to ensure the integration of the care process into the life of the patient. For this reason, the empowerment of BS patients represents a crucial need and the present work is aimed at fully exploring all the potential variables implicated in the BS patient empowerment, also highlighting major points to consider and concrete actions to be planned in the immediate future in order to implement a pragmatic facilitation of the patients’ empowerment.